The Fourth Amendment in the Twenty-First Century: Technology, Privacy, and Human Emotions - Taslitz, Andrew E. (Law and contemporary problems, 2002)
Police and local political officials in Tampa FL argued that the FaceIt system promotes safety, but privacy advocates objected to the city's recording or utilizing facial images without the victims' consent, some staging protests against the FaceIt system. Privacy objects seem to be far more widely shared than this small protest might suggest